Increasing Household Revenues Through Hydroponic Agricultural as Sustainable Agricultural Efforts - Ni Wayan Suryathi; Ni Made Delly Resiani (Warmadewa University Press, 2017)
The aims of the study were to analyze the increase in household income of hydroponics doers, to analyze how much increase in income obtained by hydroponic doers through the transfer of hydroponic farming technology in Bali Province and whether hydroponic agriculture can be made into sustainable agriculture.The study was conducted in Bali Province. Study time March-June 2017. Data collection method in this research was through survey and interview. The variables observed in this study were household income from hydroponic farming. The survey and interview data were analyzed by quantitative method by calculating all initial investment, income per harvest, the amount of other costs during one harvest. The quantitative data, then qualitatively explained to give explanation and the meaning of the numbers obtained from the quantitative calculation. The results of the analysis indicate that farming hydroponic systems can increase or be able to provide additional income to households. Therefore, through hydroponic farming, sustainable agriculture efforts will be realized. The increased income can be calculated by comparison of initial investment of Rp.5,000,000.00, compared to income derived from the sale of the vegetables. The income consists of: 1) kale vegetable, per one harvest (3 months) of 10 kg Rp.50,000.00= Rp.500,000.00. In one year, 3 times harvest= Rp.1,500,000.00. 2) Lettuce income three times harvest in one year 10 kg x Rp.75,000.00= Rp.750,000.00.(3 times harvest/year). Then, the total income/year of the hydroponic plant is Rp.2,250,000.00. Costs incurred for 1 year for both vegetable plants is Rp.400,000.00. Income difference and expense of Rp.1,850,000.00 - depreciation Rp.715,000.00 (7 years benefit period)= net income Rp.1,135,000.00. If the investment period is 7 years, the net value for 7 years x Rp.1,135,000.00= Rp.7,945,000.00 – Rp.5,000,000.00 (initial investment)= Rp.2,945,000.00. The conclusion that can be drawn that household income from hydroponic cultivation is profitable, with an income value greater than the costs incurred (revenue>cost). Keywords: increased income, hydroponic